Freedom is Not Free?: Posthumanist, Ecological Reflections on Christian Freedom and Responsibility - Rowe, Terra Schwerin (Dialog, 2015)
Philosophers aligned with a kind of posthumanism emphasize the modern, modern human's freedom and ethics are founded on a break from all ties to animality and materiality. Highlighting the posthumanist work of Jacques Derrida, Donna Haraway, and Karen Barad, this article aligns key insights of Dietrich Bonhoeffer's work, such as his pervasive concept of sociality, with the call for a more ecologically embedded humanity. The resulting reconstruction of Christian freedom is profoundly Christological and sacramental: freedom-for the other comes in, with, and throughnot apart fromboth the divine and created other.